Implementasi Algoritma Fisher Yates pada Game 3D Petualangan Menyelamatkan Binatang - Yulyanto Yulyanto; Dina Permana Dewi (Universitas Kuningan, 2020)
Abstrack : Many types of games developed by Indonesian game developers such as action games, fight games, and adventure games. Adventure games that take the theme of animals at this time is suitable to be developed considering the rampant hunting of rare animals that are protected. A good randomization method is very important in the development of an application or game. Many methods of randomization that can be used, one of them is Fisher Yates method or commonly known as Fisher Yates algorithm. The advantages of the Fisher Yates algorithm are the effectiveness of the randomization method and its optimal algorithmic complexity. Fisher Yates Algorithm can randomize the location of an animal object in an animal-saving adventure game. In addition to entertainment Animal adventure game also provides knowledge to the users to recall animals in Indonesia, the existence of these animals is increasingly reduced, because human behavior is caused by the scarcity of animals that must be preserved. Therefore, in this game, the writer implements Fisher Yates algorithm to randomize the location of animals that must be found by the users. This game is built using the software Unity 3D and C# programming language. Based on the test results using the black box method, the features contained in the game can run in accordance with the desired.Keywords : Animals, Fisher Yates Algorithm, Game, Unity 3D